Detection of Anti-Thyroglobulin and Anti-Thyroid Peroxidase Autoantibodies Related with Epstein-Barr Virus Infection in Thyroiditis Patients - Sahib, Noor Al-Huda Fadhil; Mohammed, Kareem Ghali (Medical Science Journal for Advance Research, 2024)
Background: Thyroiditis is a comprehensive term that includes many clinical diseases marked by inflammation and harm to cells in the thyroid gland. These anomalies can arise due to a range of reasons, including radiation exposure, microbial infection, or the occurrence of autoimmune thyroid diseases (AITDs) such as Hashimoto's thyroiditis (HT) and Graves' disease (GD). The cross-sectional study aimed to investigate the relationship between autoantibodies (anti-thyroglobulin and anti-thyroid peroxidase) and Epstein-Barr virus (EBV) infection. The study involved 100 patients afflicted with Thyroid dysfunction can be detected through a physical examination and certain tests. The concentrations of thyroid hormones (3,5,3′-triiodothyronine (T3) and thyroxine (T4)) and thyroid-stimulating hormone (TSH) were measured to determine the patients who have hypothyroidism or hyperthyroidism. Then the patients determined which of them had AITDs by the detection estimation of anti-thyroid antibodies (anti-thyroid peroxidase (anti-TPO) and anti-thyroglobulin (anti-TG). The tests were separated into two groups (Graves and Hashimoto). Additionally, EBV was investigated by the detection of Epstein Barr nuclear antigen-1 (EBNA-1) IgG in the sera of patients by Enzyme-Linked Immunosorbent Assay (ELISA). The present results show the mean level of serum Total EBNA-1 IgG is 9.78 ± 3.35 and 9.93 ± 4.33 in patients with HT and patients with GD, with no significant difference at (P < 0.877). The findings demonstrate a significant difference and positive association between EBNA-1 IgG and anti-TPO (r= 0.454, p= 0.001), as well as between EBNA-1 IgG and anti-TG (r= 0.279, p= 0.039) in patients diagnosed with HT. In patients with GD, there is a strong positive association between EBNA-1 IgG and anti-TPO level (r= 0.436, p= 0.001), as well as between EBNA-1 IgG and anti-TG level (r= 0.322, p= 0.031). Conclusion: Detecting anti-viral (EBNA-1 IgG) antibodies in serum samples from patients provides proof of the virus being present in the patient's tissue, which could contribute to the development of thyroiditis. There is a significant difference and positive association relationship between the levels of anti-viral (EBNA-1 IgG) antibodies and the levels of autoantibodies (anti-TPO and anti-TG) in HT, and GD.